Kebijakan pendidikan di SMA Al-Hidayah Medan - Ocha Febriyanti; Wahyu imellya pratiwi (Reflection : Islamic Education Journal, 2024)
Education policy is a policy related to the field of education in the process of building an educational vision and mission to achieve educational goals through strategic stages of education implementation. This research aims to describe educational policies regarding the policies for using different programs at Al-Hidayah High School in classes X, XI and XII. However, researchers here focus more on discussing independent learning programs. Class curriculum This research uses qualitative methods, descriptive research type. Data was collected through observation, interviews and note-taking techniques with a focus on data related to the use of the independent program and Al-Hidayah High School as a driving school. The research results show that when a school is selected as a driving school, the school will implement an independent learning program. As a driving school, all learning activity policies utilize P5 (Increasing the Profile of Pancasila Students) which uses a student-based learning approach. Thus, all regulations related to the independent program implemented at Al-Hidayah High School are in accordance with the school culture and the current personality conditions of students.